Sports finance and management : real estate, entertainment, and the remaking of the business - Winfree, Jason (Jason A.); Rosentraub, Mark S., 1950- (CRC Press, 2012)
This definitive text on sports management and finance focuses on how the modern sports team has evolved. Addressing the fact that the 21st Century sports team has turned to a real estate development, media, and entertainment corporation, this book focuses on the how and why of the change, rather than traditional finance topics such as borrowing money, ticket pricing, and player compensation. It includes an assessment of ownership structures and discusses real estate development, facility designs, and their fit into urban centers.